2021
DOI: 10.1093/advances/nmab039
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Food Prescription Programs and their Impact on Dietary Behavior and Cardiometabolic Risk Factors: A Systematic Review and Meta-Analysis

Abstract: The enormous burden of diet-related chronic diseases has prompted interest in healthy food prescription programs. Yet, the impact of such programs remains unclear. The aim of this study was to conduct a systematic review of healthy food prescription programs and evaluate their impact on dietary behavior and cardiometabolic parameters by meta-analysis. A systematic search was carried out in Medline, Embase, Scopus, and Cochrane Central Register of Controlled Trials databases since their inception to 3 January, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 87 publications
8
81
2
3
Order By: Relevance
“…Food prescription programs that operate collaboratively between healthcare and social services are fast gaining popularity in the U.S., with a recent meta-analysis demonstrating significant positive impacts on obesity and diabetes outcomes [25]. However, a major limitation identified in the meta-analysis was the lack of rigor in study designs used and small sample sizes [25]. There was also significant heterogeneity in the nutrition educational components of these food prescription programs.…”
Section: Discussionmentioning
confidence: 99%
“…Food prescription programs that operate collaboratively between healthcare and social services are fast gaining popularity in the U.S., with a recent meta-analysis demonstrating significant positive impacts on obesity and diabetes outcomes [25]. However, a major limitation identified in the meta-analysis was the lack of rigor in study designs used and small sample sizes [25]. There was also significant heterogeneity in the nutrition educational components of these food prescription programs.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Moreover, a recent metaanalysis of 13 studies found that healthy food prescription programmes may increase fruit and vegetable intake by 0.8 servings/day, reduce BMI by 0.6 kg/m 2 and reduce A1C by 0.8%, although the certainty of the evidence was rated as very low to moderate. 60 Qualitative data similarly suggest patients and care providers perceive financial, dietary and health benefits from these programmes, and support their ongoing delivery. 43 50 61-63 Food prescription programmes also appear to be cost-effective, with one recent modelling study indicating that a national healthy food prescription incentive programme in the USA could eliminate US$100.2 billion in healthcare costs if implemented over the lifetime of beneficiaries.…”
Section: Introductionmentioning
confidence: 93%
“…Despite some promising initial findings, major knowledge gaps remain pertaining to the impact and optimal implementation of healthy food prescription programmes. 60 Most prior studies have been small and uncontrolled, and have examined a small number of self-reported outcomes using brief dietary 44 45 48 63 65 and/or food insecurity screeners, 47 50–53 and/or short descriptive surveys, 44 61 63 rather than objective clinical outcomes. The majority of prior programmes have also subsidised the purchase of fruits and vegetables alone, without considering the relevance of entire dietary patterns to blood glucose levels and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 systematic review on food-insecurity interventions in healthcare settings, including PPR, found no effect on FVI when individual studies were pooled, while overall impact on health or healthcare utilization could not be determined due to variability in measures [17]. Finally, a recent meta-analysis on PPR found a 22% increase in FVI among participants when estimates were pooled; however, the authors cautioned that considerable heterogeneity and other methodological limitations preclude causal inference [27].…”
Section: Evidence About the Impact Of Financial Incentives For Fvsmentioning
confidence: 99%